Analisis Kestabilan Lereng Menggunakan Metode Bishop Pada Area Penambangan di PT. Ghaniyyah Nusantara Indah Jorong Gantiang Baruak Lubuak Aluang Sumatera Barat - pinto prinanda; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Ghaniyyah Nusantara Indah is one of the companies engaged in the procurement of goods and services which was founded in July 2018 in the city of Padang, one of the companies engaged in the clay mining business in the city of Padang. Located in Joronggantiang Baruak, Lubuk Alung, West Sumatra. PT. Ghaniyyah Nusantara Indah produces when the slopes formed as a result of the mining process or which are a means of supporting mining operations are unstable, it can cause disruption to production activities, as well as endangering work safety. The actual geometry in the field has an overal slope height of 18,064 m with a slope of 69° and the actual slope value for saturated slope is 1.086. This study aims to plan the geometry of the overal slope to obtain a safe slope FK value of 1.25.This research was conducted using the Bishop method to obtain the FK value of the overal slope. The actual slope geometry is changed, for the overall slope height is 18.064 m with an angle of 69˚ so that the FK value in saturated condition is 1.086. Furthermore, slope modification was carried out by making a bend on the slope using the Bishop method and the FK value for the overall slope in a saturated condition was 1,264. From the data analysis, the results for single slope 1 with a height of 7,982 obtained FK in a saturated condition of 1,938, while for single slope 2 with a height of 10,081 obtained FK in a saturated condition of 2,048. So it can be concluded that after redesigning the slope geometry using the Bishop method, the slope can be declared in a safe condition.